2016
DOI: 10.1097/ta.0000000000001000
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of law enforcement–related injuries in the United States

Abstract: Epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 1 publication
1
21
0
Order By: Relevance
“…On the other hand, this research also tends to focus more on characteristics of the events themselves, and is often more detailed with regard to pre-cursors of force than is typical of medical scholarship. Some of this research is focused at the national-level from an epidemiological or public health framework (e.g., Chang et al., 2016; Miller et al., 2017), while other studies conducted at the agency-level focus more on determining the situational factors and other correlates of injury to subjects and officers (e.g., Castillo et al., 2012), as well as specific concerns such as mental health status (Morabito & Socia, 2015; Rossler & Terrill, 2017). A sizeable body of work focuses specifically on Conducted Energy Devices (CEDs) and OC Spray, and their role in injury or injury reduction as well as their overall effectiveness (e.g., Brandl & Stroshine, 2017; Jenkinson et al., 2006; MacDonald et al., 2009; Paoline et al., 2012; Smith et al., 2007; Taylor & Woods, 2010; Terrill & Paoline, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, this research also tends to focus more on characteristics of the events themselves, and is often more detailed with regard to pre-cursors of force than is typical of medical scholarship. Some of this research is focused at the national-level from an epidemiological or public health framework (e.g., Chang et al., 2016; Miller et al., 2017), while other studies conducted at the agency-level focus more on determining the situational factors and other correlates of injury to subjects and officers (e.g., Castillo et al., 2012), as well as specific concerns such as mental health status (Morabito & Socia, 2015; Rossler & Terrill, 2017). A sizeable body of work focuses specifically on Conducted Energy Devices (CEDs) and OC Spray, and their role in injury or injury reduction as well as their overall effectiveness (e.g., Brandl & Stroshine, 2017; Jenkinson et al., 2006; MacDonald et al., 2009; Paoline et al., 2012; Smith et al., 2007; Taylor & Woods, 2010; Terrill & Paoline, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…National-level research has provided evidence on injury trends, primarily derived from Centers for Disease Control (CDC) data. For example, Chang et al. (2016) examined national data for the period 2003–2011, and noted that while the Federal Bureau of Investigation’s (FBI) Law Enforcement Officers Killed and Assaulted (LEOKA) statistics showed a decline in assaults on police officers during that time period, CDC data showed an increase in hospital admissions and nonfatal injuries to citizens related to police action.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 When the wounding mechanism is a firearm, White and Black patients are more likely to die than Hispanic patients. 2 These pre-existing studies all call for further study of this important public health problem to better understand injuries sustained during interaction with law enforcement to begin to work toward injury prevention and mitigation.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature suggests that there are racial differences among patients injured by civilians as compared with those injured during LI 1 and that outcomes after LI-associated injuries may vary by race. 2 One study found that despite comparable injury severity among civilian interpersonal violence (CIV) and injuries sustained during LI, patients injured during LI may have worse outcomes. 3 It is clear that injuries sustained during the course of LI differ in substantial ways from those inflicted on civilians by other civilians.…”
mentioning
confidence: 99%
“…The International Classification of Diseases, Ninth Revision, Clinical Modification, includes external cause-ofinjury codes identifying injuries owing to contact with law enforcement (E970-E978). Using these codes, prior studies have identified 715 118 nonfatal injuries, 3958 hospitalizations, and 3156 deaths between 2003 and 2011 from US Centers for Disease Control and Prevention data and the Nationwide Inpatient Sample, 4 and 55 400 fatal and nonfatal injuries in 2012 from the Vital Statistics mortality census, Nationwide Inpatient and Emergency Department Samples, and journalists' reports. 5 In this study, we used a nationally representative database to determine whether the incidence of emergency department (ED) visits for injures by law enforcement increased relative to total ED visits from 2006 to 2012.…”
Section: Us Emergency Department Encounters For Law Enforcement-assocmentioning
confidence: 99%